User Experience Influence On Purchase Intention In Tokopedia - Prayogi Prasetyoputra Pramono; I Gede Sanica (Eduvest - Journal of Universal Studies, 2025)
This study aims to analyze the relationship between the influence of user experience on purchase intention in Tokopedia using the Technology Acceptance Model (TAM) framework. Tokopedia is one of the well-known e-commerce platforms in Indonesia, but along with the increasing progress in the field of information and the internet, as well as the increasing criticality of the public, Tokopedia needs to consider many factors that can increase shopping interest (purchase intention) on the Tokopedia platform, one of which is user experience. The population of this study is the entire Balinese community which totals 4,344,554 people as of December 2023. The sample was determined using a non-probability sampling technique with a total of 200 samples. The data collection technique uses the distribution of questionnaires using google forms. Data analysis was carried out by SEM-PLS analysis. The results of this study show that user experience has a positive and significant effect on the buying interest of Tokopedia customers. User experience has a positive and significant effect on the user satisfaction of the Tokopedia application. User experience has a positive and significant influence on the purchase intention of e-commerce users on Tokopedia with user satifation as a mediating variable. User experience has a positive and significant effect on the user trust of the Tokopedia application. And user experience has a positive and significant influence on the purchase intention of e-commerce users on Tokopedia with user trust as a mediating variable.